Comparative analysis of managerial strategies for enhancing teacher motivation in Public and Private Schools - Zhengliang Gao; Guangjiao Hu; Shahla Akram; Mehboob Ul Hassan; Muhammad Farrukh Shahzad; Sajjad Ahmad Jan (Scientific Reports)
Abstract The purpose of this study is to examine the strategies used by Pakistani school principals in both public and private institutions to improve teacher motivation. Data were gathered from 150 teachers across three cities in Pakistan: Lahore, Multan, and Faisalabad. The study used a mixed-methods approach, employing both closed-ended and open-ended questionnaires for teachers. Additionally, semi-structured interviews were conducted with 30 school principals to provide deeper insights. Principal component analysis (PCA) and inferential statistics were used in quantitative analysis, and thematic analysis was used to examine qualitative data. The results show that public and private schools differ significantly in resource allocation, motivational techniques and leadership styles. Private school teachers were more motivated due to their greater flexibility, individual support, and external recognition programs. Public schools, on the other hand, struggled with a lack of individual instruction, strict structures and scarce resources. The study highlights the importance of managerial strategies for increasing teacher motivation. Policymakers should consider ways to provide greater support to public schools, with a particular focus on developing more responsive leadership structures and providing resources for teacher professional development and engagement.